Do childhood depressive symptoms interfere with intelligence in adulthood? - Lima, Janielle Ferreira de Brito; Lima, Raina Jansen Cutrim Propp; Batalha, Mônica Araújo; Silva, Antônio Augusto Moura da; Ribeiro, Marizélia Rodrigues Costa; Batista, Rosângela Fernandes Lucena (Revista de Saúde Pública, 2023)
OBJECTIVE: To investigate the effects of depressive symptoms in childhood on the intellectual development of young adults. METHODS: Study conducted with a birth cohort of São Luís, Maranhão, Brazil, composed of 339 participants evaluated between 7 and 9 years and between 18 and 19 years. Structural equation modeling (young adult education, sex, race/color) and childhood variables (nutritional status, depressive symptoms, cognitive function, head of household’s and mother’s education, family income) were used. In addition, head of household’s occupation, mother’s age, and presence of partner were tested as determinants of adults’ intelligence quotient (IQ). RESULTS: Presence of depressive symptoms in childhood triggered a reduction of 0.342 in standard deviation (SD) and -3.83 points in the average IQ of adults (p-value < 0.001). Cognitive function in childhood had a total and direct positive effect (standardized coefficient [SC] = 0.701; p-value < 0.001) on IQ, increasing 7.84 points with each increase in level. A positive indirect effect of child nutritional status (SC = 0.194; p-value = 0.045), head of household’s (SC = 0.162; p-value = 0.036), and mother’s education was identified, the latter mediated by cognitive function in childhood (SC = 0.215; p-value = 0.012) on the IQ of young people. CONCLUSION: Presence of depressive symptoms in childhood triggered a long-term negative effect on intelligence, reducing the IQ score in adulthood.